PENGARUH KEPEMILIKAN MANAJERIAL UKURAN PERUSAHAAN, LEVERAGE, DAN GROWTH OPPORTUNITIES TERHADAP KONSERVATISME AKUNTANSI - Esa Anti Ursula; Vidya Vitta Adhivinna (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
One of the principle in create a financial report is the accounting conservatism principle. Conservatism is said to more anticipating the loss than gain. This study aims to determine how the effect of managerial ownership, firm size, leverage, and growth opportunities to accounting conservatism. The data used in this study is secondary data from 10 manufacturing company sub sector consume listed on the Indonesia Stock Exchange for the period 2012-2017. Samples were selected using purposive sampling method. Technique of analyzing data used is the test multiple linear regression analysis with SPSS version 16. The result showed that simultaneous managerial ownership, firm size, leverage, and growth opportunities together have influence on accounting conservatism. Partially, firm size, leverage, and growth opportunities have influence on accounting conservatism, while managerial ownership has no influence on accounting conservatism. Keywords: Conservatism Accounting, Managerial Ownership, Firm Size, Leverage, Growth Opportunities